La démocratie et le statut des femmes au Liban - Bdeir, Leila (Université du Québec à Montréal, 2005)
Keywords: IREF; approches et analyses; asie; discipline; femmes* politiques; liban; militance; mouvements féministes; mémoires/thèses; régions géographiques; science politique; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Emotions and social movements - Flam, Helena; King, Debra (Routledge, 2005)
Addressing issues of emotion in social movements, this internationally oriented volume will appeal to both sociologists and political activists given its broad approach and unique emphasis on emotions in protest, dissent and social movements.
Keywords: 1900-1999; care; discipline; militance; mouvements sociaux; outils; ouvrages de références; périodes historiques; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions